2023
DOI: 10.1111/1756-185x.14601
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of joints involved in rheumatoid arthritis

Abstract: Finite element analysis of joints involved in rheumatoid arthritisDear Editor, We read with great interest the article by Figueiredo et al 1 regarding lower hand grip in patients with rheumatoid arthritis (RA), for which it was demonstrated that patients with RA presented with lower bone strength of 2nd metacarpophalangeal (MCP) joint through a finite element analysis (FEA) using high-resolution peripheral quantitative computed tomography (HR-pQCT) scan. We appreciate the authors' valuable contribution to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…2 It is worth noting that patients with OA who had comorbid psychiatric conditions might be prescribed SNRIs, potentially serving as a proxy for mental health that could significantly influence social behavior and participation. Additionally, socioeconomic status was addressed in the study, but other prevalent elderly diseases such as hypertension, 3,4 hyperlipidemia, 5 dementia, 6 sleep disorders, 7 and rheumatoid arthritis, 8 which frequently coexist with OA, and other conditions such as the coronavirus disease 2019 (COVID-19) 9,10,11 that can profoundly impact social participation,…”
Section: Social Activity Physical Exercise and Health-related Quality...mentioning
confidence: 99%
“…2 It is worth noting that patients with OA who had comorbid psychiatric conditions might be prescribed SNRIs, potentially serving as a proxy for mental health that could significantly influence social behavior and participation. Additionally, socioeconomic status was addressed in the study, but other prevalent elderly diseases such as hypertension, 3,4 hyperlipidemia, 5 dementia, 6 sleep disorders, 7 and rheumatoid arthritis, 8 which frequently coexist with OA, and other conditions such as the coronavirus disease 2019 (COVID-19) 9,10,11 that can profoundly impact social participation,…”
Section: Social Activity Physical Exercise and Health-related Quality...mentioning
confidence: 99%
“…For instance, the 28-joint Disease Activity Score (DAS28) is a useful tool for assessing disease activity in patients with RA, as it evaluates 28 tender and swollen joints, general health, and levels of acute phase reactants such as erythrocyte sedimentation rate or C-reactive protein. [28][29][30][31][32][33] Similarly, the Knee Injury and Osteoarthritis Outcome Score (KOOS) is a suitable measurement tool for assessing OA in young and old adults, with adequate internal consistency, test-retest reliability, and construct validity. [34][35][36][37] Furthermore, the Lysholm score and the International Knee Documentation Committee (IKDC) Subjective Knee Form are reliable and valid instruments that should be considered, especially for patients with OA related to ligament or meniscus injury.…”
mentioning
confidence: 99%
“…If a link is established, screening for HLA and tests for K. pneumoniae-derived antigens may facilitate the diagnosis of AS, as similar to how such approaches are used for various other diseases. 10,21,22 Additionally, studies have also demonstrated the association between enteric pathogens and inflammatory arthritis, including rheumatoid arthritis, 15,[23][24][25][26] psoriatic arthritis, 27 and spondyloarthritis. 5,21 This underscores the significance of this topic and the need to further elucidate the role of K. pneumoniaein the etiology and pathogenesis of AS.…”
mentioning
confidence: 99%